THE ROLE OF CUSTOMER SATISFACTION IN MEDIATING THE INFLUENCE OF BRAND IMAGE AND PRODUCT QUALITY ON REPURCHASE INTENTION(STUDY ON CUSTOMERS OF OASIS BRAND BOTTLED DRINKING WATER IN BALI) - Indra Mahardika; Tjokorda Gde Raka Sukawati; Ni Wayan Sri Suprapti; I Gusti Ngurah Jaya Agung Widagda (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The Bottled Drinking Water industry is experiencing rapid growth today in line with the high demand for clean water for consumption and the availability of clean water in several areas is very limited (Dewi, 2019). PT Oasis Waters International Bali Branch is one of the bottled water producers under the Oasis brand that provides a variety of products to meet consumer needs. The high level of competition in the bottled water market in Bali makes management need to improve competitive advantages, product quality and brand image to maintain customer satisfaction and consumer repurchase intentions. This study analyzes the role of customer satisfaction in mediating brand image and product quality on the repurchase intention of Oasis bottled water customers in Bali. This study involved 150 respondents by applying the technique of proportionate stratified random sampling in determining the sample. The results of this study show that brand image and product quality have a significant positive effect on customer satisfaction and repurchase intention and customer satisfaction is able to mediate the influence of product quality and brand image on repurchase intention.